Calsequestrins New Calcium Store Markers of Adult Zebrafish Cerebellum and Optic Tectum - Sandra Furlan; Marina Campione; Marta Murgia; Marta Murgia; Simone Mosole; Francesco Argenton; Pompeo Volpe; Alessandra Nori (Frontiers Media S.A., 2020)
Calcium stores in neurons are heterogeneous in compartmentalization and molecular composition. Danio rerio (zebrafish) is an animal model with a simply folded cerebellum similar in cellular organization to that of mammals. The aim of the study was to identify new endoplasmic reticulum (ER) calcium store markers in zebrafish adult brain with emphasis on cerebellum and optic tectum. By quantitative polymerase chain reaction, we found three RNA transcripts coding for the intra-ER calcium binding protein calsequestrin: casq1a, casq1b, and casq2. In brain homogenates, two isoforms were detected by mass spectrometry and western blotting. Fractionation experiments of whole brain revealed that Casq1a and Casq2 were enriched in a heavy fraction containing ER microsomes and synaptic membranes. By in situ hybridization, we found the heterogeneous expression of casq1a and casq2 mRNA to be compatible with the cellular localization of calsequestrins investigated by immunofluorescence. Casq1 was expressed in neurogenic differentiation 1 expressing the granule cells of the cerebellum and the periventricular zone of the optic tectum. Casq2 was concentrated in parvalbumin expressing Purkinje cells. At a subcellular level, Casq1 was restricted to granular cell bodies, and Casq2 was localized in cell bodies, dendrites, and axons. Data are discussed in relation to the differential cellular and subcellular distribution of other cerebellum calcium store markers and are evaluated with respect to the putative relevance of calsequestrins in the neuron-specific functional activity.